Lower late-life body-mass index is associated with higher cortical amyloid burden in clinically normal elderly - Hsu, David C. (J Alzheimers Dis, 2016)
BACKGROUND: Lower body-mass index (BMI) in late life has been associated with an increased risk of dementia, and weight loss has been associated with more rapid decline in Alzheimer disease (AD) dementia. OBJECTIVE: To explore the association between BMI and cortical amyloid burden in clinically normal (CN) elderly at risk for AD dementia. METHODS: Cross-sectional analyses were completed using baseline data from the Harvard Aging Brain Study, consisting of 280 community-dwelling CN older adults aged 62–90. Assessments included medical histories and physical exam, Pittsburgh compound B (PiB) positron emission tomography (PET) amyloid imaging, and apolipoprotein E ɛ4 (APOE4) genotyping. For the primary analysis, a general linear regression model was used to evaluate the association of BMI with PiB retention. Covariates included age, sex, years of education, and APOE4 carrier status. Secondary analyses were performed for BMI subdivisions (normal, overweight, obese), APOE4 carriers, and BMI × APOE4 interaction. RESULTS: In the primary analysis, greater PiB retention was associated with lower BMI (β=−0.14, p=0.02). In the secondary analyses, APOE4 carrier status (β=−0.27, p=0.02) and normal BMI (β=−0.25, p=0.01), as opposed to overweight or obese BMI, were associated with greater PiB retention. The BMI × APOE4 interaction was also significant (β=−0.14, p=0.04). CONCLUSIONS: This finding offers new insight into the role of BMI at the preclinical stage of AD, wherein lower BMI late in life is associated with greater cortical amyloid burden. Future studies are needed to elucidate the mechanism behind this association, especially in those with lower BMI who are APOE4 carriers.